Evaluating the financial performance of Iraqi banks through a matrix analysis (performance-importance): An applied study on a sample of commercial banks listed on the Iraq Stock Exchange for the period (2006-2020) - Abdel-Aali Karim Al-Aboudi, Abbas; makee mahmood Albanaa, Zainab (Iraqi Journal for Administrative Sciences, 2024)
The research aims to assess the financial performance of Iraqi banks by analyzing the performance-importance matrix. This examination is based on five commercial banks listed in the Iraqi Stock Exchange for the period from 2006 to 2020, which are (Commercial Bank, Investment Bank, Sumer Bank, Credit Bank, United Bank), where Its financial data was obtained from its annual reports published on the Iraq Stock Exchange website, and the research applied the analysis of financial performance indicators represented by (profitability, liquidity, risk) to determine the financial performance of the research sample banks and then evaluate their performance through the analysis of the performance matrix - the importance of testing a series One of the hypotheses that emerged from a review of the previous literature. The results of the research, by analyzing the impact and importance of the matrix variables (performance-importance) through the Smart PLS statistical program, show that banks witnessed an increase in financial performance in the period (2016-2020) due to their positive performance during the research period, which reflected positively on profitability. And in order to improve the levels of financial performance of banks, the researcher recommends managers to evaluate financial performance through the performance-importance matrix on a regular basis because this approach allows managers to improve their management strategies because it indicates the main weaknesses that require immediate treatment.